A method of air target recognition based on combined-rules. Issue 1 (1st April 2022) - Zhang, Zhen; Fang, Fengtang; Xing, Yupeng; Fu, Bin
Abstract: In order to improve the authenticity, reliability and accuracy of air target identification in complex situation, a processing method based on combined-rules is proposed to further enhance the automation degree of air target identification among various air target identification methods. Rule combination and conflict resolutionare used to reduce the workload of human intervention and manual judgment and make target recognition more rapid and accurate.